Bad Men, Good Men, and Loving Women: Gender Constructions in British State Messaging on Counterterrorism, Countering Violent Extremism and Preventing Violent Extremism - Toros, Harmonie (Terrorism and political violence, 2025)
The United Kingdom presents itself as a leader in counterterrorism (CT), countering violent extremism (CVE) and preventing violent extremism (PVE). The Action Counters Terrorism Campaign is a public-facing campaign of the U.K. government aimed at raising the public’s awareness of how it can support its CT/CVE/PVE efforts. A narrative analysis of the campaign’s YouTube channel (2017–2020) reveals a clear dominant narrative that “ordinary people” can assist in CT/CVE/PVE by being alert and following basic rules (such as Run, Hide, Tell). However, a gendered narrative analysis reveals far more surprising results: The terrorist threat is understood as exclusively male and only men are viewed as at risk of radicalization. Women are predominantly portrayed in relation to men in their lives. Through their love and care, women can support efforts to save men by noticing when “something is wrong.” This article reveals how the gendered constructions of the British awareness campaign are so engrained in a powerful metanarrative of gender and political violence that they ignore even widespread public security debates, such as those surrounding British girls and women joining ISIS. It concludes that a narrative analysis must include a gendered analysis to understand the political and security implications of CT/CVE/PVE narratives.